2017
DOI: 10.1108/jrf-12-2016-0156
|View full text |Cite
|
Sign up to set email alerts
|

The impact of sovereign rating events on bank stock returns

Abstract: Purpose This paper aims to investigate the impact of sovereign rating signals on domestic banks’ stock returns in a European context. Design/methodology/approach The author uses an event study technique to measure short-term bank stock abnormal returns that result from domestic positive or negative sovereign rating events. Then, test results from the univariate event studies are further scrutinised with the bank- and sovereign-related factors related to cross-sectional variations in abnormal bank returns. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 93 publications
1
2
0
Order By: Relevance
“…The results of other studies that support the results of this study through univariate tests show that positive sovereign rating events do not cause significant bank stock price reactions, while negative events are associated with negative stock price effects on domestic banks (Hu, 2017).…”
supporting
confidence: 87%
“…The results of other studies that support the results of this study through univariate tests show that positive sovereign rating events do not cause significant bank stock price reactions, while negative events are associated with negative stock price effects on domestic banks (Hu, 2017).…”
supporting
confidence: 87%
“…They showed how past and current data influenced the ratings. Hu and Hu [23] studied the effect of sovereign ratings on bank stock returns in the European Union. They found that positive sovereign ratings did not lead to a bank's stock price reaction; however, negative events caused negative sovereign rating events.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results of this interpretation of information will later influence decision making, if many interested parties have a pessimistic view due to bad news from the information received, then it will reduce its activities. Conversely, if interested parties look optimistic due to good news from information received, then he will strengthen his activities (Hu, 2017).…”
Section: Introductionmentioning
confidence: 99%